2012
DOI: 10.1016/j.joca.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of low intensity ultrasound (LIUS) on complete Freund's adjuvant-induced arthritis synovium

Abstract: LIUS showed a potent anti-inflammatory effect in this animal arthritis model with reduced infiltration of inflammatory cells into the synovium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 49 publications
(50 reference statements)
6
60
0
Order By: Relevance
“…One possible reason is that the mechanical function of LIPUS enhanced blood and lymph circulation in the lesions and sped up cleaning the deforming tissue by enhancing the activity of macrophages to reduce inflammation (Chen et al 2010). Another possible reason is that LIPUS has the antiinflammatory effect with reduced infiltration of inflammatory cells in the defect area (Chung et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that the mechanical function of LIPUS enhanced blood and lymph circulation in the lesions and sped up cleaning the deforming tissue by enhancing the activity of macrophages to reduce inflammation (Chen et al 2010). Another possible reason is that LIPUS has the antiinflammatory effect with reduced infiltration of inflammatory cells in the defect area (Chung et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed insignificant change in TNF-alpha between the three groups used. In line with us, Assis et al reported decrease in IL1-beta with 50 mW laser therapy applied to [19]. The role of IL1-beta in amplifying the production of other cytokines such as IL-6, TNF-alpha and INF-gamma driving the production of matrix metalloproteinases inducing a cascade of destructive and inflammatory responses in osteoarthritis had been reported [20].…”
Section: Discussionmentioning
confidence: 53%
“…Piroxicam and DMSO are applied to the US head onto the skin. Duration of the treatment which depends on the treatment area, if there is a large treatment area, it can be divided into equal half's, and the treatment has been commenced following that [10] local skin anesthesia, skin burns, mental illness, and skin irritation, in particular, treatment area are contraindicated for phonophoresis.…”
Section: Introductionmentioning
confidence: 99%